2010
DOI: 10.1007/s10237-010-0268-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement and modeling analysis on mechanical properties of incudostapedial joint

Abstract: The incudostapedial (IS) joint between the incus and stapes is a synovial joint consisting of joint capsule, cartilage, and synovial fluid. The mechanical properties of the IS joint directly affect the middle ear transfer function for sound transmission. However, due to the complexity and small size of the joint, the mechanical properties of the IS joint have not been reported in the literature. In this paper, we report our current study on mechanical properties of human IS joint using both experimental measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…In particular for the ISJ, a portion of elastic ligamentous tissue is usually interposed between the two adjacent ossicles, whose characteristics, in terms of density and Young's modulus, are 1.2 × 10 3 kg/m 3 and 0.6 MPa respectively [4,46]. However, recently two studies on the ISJ modeling were presented, one on a sub-structured FE model of the cat joint [51], the other one on an experimentally calibrated FE model with hyperelastic tissue characterization [52].…”
Section: Joint Modelingmentioning
confidence: 98%
“…In particular for the ISJ, a portion of elastic ligamentous tissue is usually interposed between the two adjacent ossicles, whose characteristics, in terms of density and Young's modulus, are 1.2 × 10 3 kg/m 3 and 0.6 MPa respectively [4,46]. However, recently two studies on the ISJ modeling were presented, one on a sub-structured FE model of the cat joint [51], the other one on an experimentally calibrated FE model with hyperelastic tissue characterization [52].…”
Section: Joint Modelingmentioning
confidence: 98%
“…1 show details of the ISJ from longitudinal (axis from incus to stapes) and transvers views of configurations of the articular cartilage, meniscus, synovial fluid, and joint capsule that connects the lenticular process and stapes head. The dimensions of all components are listed in Table 1 based on the data reported in the literature [9,11]. In the FE model of ISJ, the cartilage and meniscus were assigned as linear elastic Solid 45 elements in ANSYS.…”
Section: Finite Element Modeling Of Isj Microstructurementioning
confidence: 99%
“…To identify the mechanical properties of joint components and determine the effects of components on vibration transduction through the middle ear ossicular chain, we created 6 cases of different mechanical properties for joint capsule, cartilage, meniscus, and synovial fluid. Case 1 was a baseline case in which the capsule was assumed as viscoelastic material using the standard linear viscoelastic model with 3 material parameters: E 0 , E 1 , and τ 1 [11,12]. The articular cartilage and meniscus were assumed as elastic material with the Young's modulus E and Poisson's ratio .…”
Section: Mechanical Properties Of Isj Components and Fe Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary work has supported the idea that the IMJ is mobile at frequencies above 2 kHz (Gerig et al , 2015), as well as under quasi-static loading conditions (Ihrle et al , 2016). The ISJ has received relatively less scrutiny than the IMJ, though a number of studies have demonstrated that it is functionally mobile at hearing frequencies (Nakajima et al , 2005; Zhang and Gan, 2011) and that fixing it causes changes in sound transmission (Hato et al , 2003; Alian et al , 2013). …”
Section: Introductionmentioning
confidence: 99%